2012
DOI: 10.1080/1068316x.2010.508458
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure time and cognitive operations on facial identification accuracy: a meta-analysis of two variables associated with initial memory strength

Abstract: In the present study, we conducted two separate meta-analyses in order to quantify the influence on facial identification accuracy of two variables related to initial memory strength for an unfamiliar face, specifically, length of exposure at the time of encounter and encoding operations as manipulated via stimulus processing instructions. Proportion correct was significantly higher for longer (M 0 0.66) as compared to shorter exposure durations (M 0 0.53) and when participants made social judgments of faces (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 81 publications
6
42
0
2
Order By: Relevance
“…These include aspects of the witness, perpetrator, the crime event itself, or intervening events. For example, witnessing crimes under poor lighting conditions (G. Loftus, 2010), for a short amount of time (Bornstein, Deffenbacher, Penrod, & McGorty, 2012), from great distances (Lampinen, Erickson, Moore, & Hittson, 2014), or committed by someone of a different race (Meissner & Brigham, 2001) can greatly reduce identification accuracy. Long delays (or retention intervals) between the crime event and memory test may also weaken eyewitness memory (Deffenbacher, Bornstein, McGorty, & Penrod, 2008;Wheatcroft, Wagstaff, & Manarin, 2015) and, further, increase the risk of exposure to post-event information and suggestion (e.g., media reports and conversations with other witnesses), which may distort witnesses' recollections of their experiences (E. Loftus, 2005).…”
Section: Eyewitness Memory and Juror Evaluations Of Witness Evidencementioning
confidence: 99%
“…These include aspects of the witness, perpetrator, the crime event itself, or intervening events. For example, witnessing crimes under poor lighting conditions (G. Loftus, 2010), for a short amount of time (Bornstein, Deffenbacher, Penrod, & McGorty, 2012), from great distances (Lampinen, Erickson, Moore, & Hittson, 2014), or committed by someone of a different race (Meissner & Brigham, 2001) can greatly reduce identification accuracy. Long delays (or retention intervals) between the crime event and memory test may also weaken eyewitness memory (Deffenbacher, Bornstein, McGorty, & Penrod, 2008;Wheatcroft, Wagstaff, & Manarin, 2015) and, further, increase the risk of exposure to post-event information and suggestion (e.g., media reports and conversations with other witnesses), which may distort witnesses' recollections of their experiences (E. Loftus, 2005).…”
Section: Eyewitness Memory and Juror Evaluations Of Witness Evidencementioning
confidence: 99%
“…These archival results are consistent with a meta-analysis conducted by Bornstein, Deffenbacher, Penrod, and McGorty (2012) on laboratory face recognition and eyewitness studies. The authors examined the influence of exposure duration across 33 independent effect sizes reported in 25 articles.…”
Section: Eyewitness Researchsupporting
confidence: 88%
“…However, Bornstein and colleagues (2012) maintain that increasing exposure duration may influence accuracy more so on the shorter end of the spectrum. For example, greatest effects appear when durations are less than 30 seconds, whereas beyond 30 seconds a more substantial difference is required to produce equivalent effects (Bornstein et al, 2012) Overall, results from face recognition and eyewitness identification studies suggest that longer exposure duration may result in increased identification accuracy (Gross & Hayne, 1996;Leippe et al, 1991). Moreover, Burton and colleagues' IAC model (1999), although typically applied to cognitive research, implies that face recognition for familiar faces is more quickly and accurately accomplished due to semantic priming.…”
Section: Eyewitness Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Eyewitness scientists play an important role in helping legal decision makers assess eyewitness credibility and even train or prepare potential witnesses (e.g., bank tellers) to exert some control over cognitive processes of attention and encoding ( Bornstein et al, 2012 ). Video-recording of the witness's identifi cation attempt may be helpful in jurors' assessment of eyewitness accuracy ( Reardon & Fisher, 2011 ).…”
Section: Policy and Practicementioning
confidence: 99%